Math Archives (4)

Geometry Level 4

sin 1 ( x ) + sin 1 ( 2 x ) = π 3 \sin^{-1}(x)+\sin^{-1}(2x)=\dfrac{\pi}{3} Find the number of solutions of above equation. Try my set Math Archive

1 2 0 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ikkyu San
Apr 6, 2016

sin 1 x + sin 1 ( 2 x ) = π 3 cos ( sin 1 x + sin 1 ( 2 x ) ) = cos ( π 3 ) cos ( sin 1 x ) cos ( sin 1 ( 2 x ) ) sin ( sin 1 x ) sin ( sin 1 ( 2 x ) ) = 1 2 ( 1 x 2 ) ( 1 4 x 2 ) x ( 2 x ) = 1 2 1 5 x 2 + 4 x 4 = 2 x 2 + 1 2 4 x 4 5 x 2 + 1 = 4 x 4 + 2 x 2 + 1 4 7 x 2 = 3 4 x 2 = 3 28 x = ± 1 2 3 7 \begin{aligned}\sin^{-1}x+\sin^{-1}(2x)=&\dfrac{\pi}3\\\cos(\sin^{-1}x+\sin^{-1}(2x))=&\cos\left(\dfrac{\pi}3\right)\\\cos(\sin^{-1}x)\cos(\sin^{-1}(2x))-\sin(\sin^{-1}x)\sin(\sin^{-1}(2x))=&\dfrac12\\(\sqrt{1-x^2})(\sqrt{1-4x^2})-x(2x)=&\dfrac12\\\sqrt{1-5x^2+4x^4}=&2x^2+\dfrac12\\4x^4-5x^2+1=&4x^4+2x^2+\dfrac14\\-7x^2=&-\dfrac34\\x^2=&\dfrac3{28}\\x=&\pm\dfrac12\sqrt{\dfrac37}\end{aligned}

But sin 1 ( x ) = sin 1 x \sin^{-1}(-x)=-\sin^{-1}x and sin 1 ( 2 x ) = sin 1 ( 2 x ) \sin^{-1}(-2x)=-\sin^{-1}(2x) . Thus, 1 2 3 7 -\dfrac12\sqrt{\dfrac37} is cannot be the value of x x implying that the value of sin 1 x + sin 1 ( 2 x ) = π 3 \sin^{-1}x+\sin^{-1}(2x)=\dfrac{\pi}3 satisfying is x = 1 2 3 7 x=\boxed{\dfrac12\sqrt{\dfrac37}} .

Hence, this equation has only one solution.


Notes:

cos ( x + y ) = cos x cos y sin x sin y \cos(x+y)=\cos{x}\cos{y}-\sin{x}\sin{y}

cos ( sin 1 x ) = 1 x 2 , 1 x 1 \cos(\sin^{-1}x)=\sqrt{1-x^2},\ -1\leq x\leq1

cos ( sin 1 ( 2 x ) ) = 1 ( 2 x ) 2 = 1 4 x 2 , 1 2 x 1 2 \cos(\sin^{-1}(2x))=\sqrt{1-(2x)^2}=\sqrt{1-4x^2},\ -\dfrac12\leq x\leq\dfrac12

sin ( sin 1 x ) = x \sin(\sin^{-1}x)=x

sin ( sin 1 ( 2 x ) ) = 2 x \sin(\sin^{-1}(2x))=2x

Graphical solution is smarter and feasible approach .

Shivam Jadhav - 5 years, 2 months ago

Log in to reply

@Shivam Jadhav Can you show how?

Anurag Pandey - 4 years, 8 months ago

Let { sin 1 ( x ) = α sin α = x sin 1 ( 2 x ) = β sin β = 2 x α + β = π 3 \begin{cases} \sin^{-1} (x) = \alpha & \Rightarrow \sin \alpha = x \\ \sin^{-1} (2x) = \beta & \Rightarrow \sin \beta = 2x \end{cases} \quad \Rightarrow \alpha + \beta = \dfrac{\pi}{3}

Now, we have:

sin β = 2 x sin ( π 3 α ) = 2 sin α 3 2 cos α 1 2 sin α = 2 sin α 3 2 cos α = 5 2 sin α tan α = 3 5 α = tan 1 3 5 sin 1 ( x ) 0.3335 rad sin 1 ( 2 x ) 0.7137 rad \begin{aligned} \sin \beta & = 2x \\ \sin \left(\frac{\pi}{3} - \alpha \right) & = 2\sin \alpha \\ \frac{\sqrt{3}}{2}\cos \alpha - \frac{1}{2} \sin \alpha & = 2 \sin \alpha \\ \frac{\sqrt{3}}{2}\cos \alpha & = \frac{5}{2} \sin \alpha \\ \Rightarrow \tan \alpha & = \frac{\sqrt{3}}{5} \\ \alpha & = \tan^{-1} \frac{\sqrt{3}}{5} \\ \Rightarrow \sin^{-1} (x) & \approx 0.3335 \text{ rad} \\ \sin^{-1} (2x) & \approx 0.7137 \text{ rad} \end{aligned}

As sin 1 ( x ) [ π 2 , π 2 ] \sin^{-1} (x) \in [-\frac{\pi}{2}, \frac{\pi}{2}] and the other solutions are in the third quadrant, there is only 1 \boxed{1} solution to the equation.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...